Fault tolerant control of a permanent magnet synchronous machine using multiple constraints Takagi-Sugeno approach - Moussaoui, Lotfi; Aouaouda, Sabrina; Rouaibia, Reda (Національний технічний університет "Харківський політехнічний інститут", 2022)
Introduction. Fault diagnosis, and fault tolerant control issues are becoming very important to ensure a good supervision of systems and guarantee the safety of human operators and equipments even if system complexity increases. Problem. In fact, the presence of faults in actuators, sensors and processes can lead to system performance degradation, system breakdown, economic loss, and even disastrous situations. Furthermore, Actuator saturation or control input saturation is probably the most usual nonlinearity encountered in control engineering because of the physical impossibility of applying unlimited control signals and/or safety constraints. Purpose. This article is dedicated to the problem of fault tolerant control for constrained nonlinear systems described by a Takagi-Sugeno model. One of the interests of this type of models is the possibility of extend some tools and methods from linear system case to the nonlinear one. The novelty of the work consists in developing a fault tolerant control algorithm for a nonlinear Permanent Magnet Synchronous Machine model using an observer based state-feedback control technique in order to enhance fault and state estimation despite actuator saturation and system disturbances. Methods. Indeed a sensor fault detection observer based residual generator is synthesized with a guaranteed L₂ performance to attenuate the external disturbances effect from one side and to maximize the residual sensitivity to faults from the other side. Based on Lyapunov function, design conditions are formulated in terms of Linear Matrix Inequalities to ensure stability of the global system. Practical value. A detailed study concerning nonlinear permanent magnet synchronous machine model, which is consolidated by simulation results, is conducted to show the used algorithm’s effectiveness guarantying fault estimation and reconfiguration of the control law to maintain stable performance even in the presence of actuator faults, external perturbation and the phenomenon of actuator saturation.

Вступ. Діагностика несправностей і питання стійкості до відмови стають дуже важливими для забезпечення хорошого контролю систем і гарантії безпеки людей-операторів і обладнання, навіть якщо складність системи зростає. Проблема. Насправді наявність несправностей у виконавчих механізмах, датчиках і процесах може призвести до зниження продуктивності системи, поломки системи, економічних втрат і навіть катастрофічних ситуацій. Крім того, насичення виконавчого механізму або насичення керуючого входу, ймовірно, є найбільш поширеною нелінійністю, що зустрічається в техніці керування через фізичну неможливість застосування необмежених керуючих сигналів та обмежень безпеки. Мета. Ця стаття присвячена проблемі стійкості до відмови нелінійних систем з обмеженнями, що описуються моделлю Такагі-Сугено. Однією з переваг цього типу моделей є можливість поширення деяких інструментів та методів з випадку лінійної системи на нелінійну. Новизна роботи полягає у розробці алгоритму управління стійкості до відмови для моделі нелінійної синхронної машини з постійними магнітами з використанням методу управління зі зворотним зв'язком станом на основі спостерігача, щоб поліпшити оцінку помилок і станів, незважаючи на насичення приводу і збурення системи. Методи. Дійсно, генератор нев'язки на основі спостерігача виявлення несправності датчика синтезується з гарантованою продуктивністю L2, щоб послабити вплив зовнішніх перешкод з одного боку та максимізувати залишкову чутливість до несправностей з іншого боку. На основі функції Ляпунова умови проєктування формулюються в термінах лінійних матричних нерівностей для забезпечення стійкості глобальної системи. Практична цінність. Детальне дослідження нелінійної моделі синхронної машини з постійними магнітами, об'єднане результатами моделювання, проводиться для демонстрації ефективності використовуваного алгоритму, що гарантує оцінку відмов та реконфігурацію закону управління для підтримки стабільної роботи навіть за наявності відмов приводу, зовнішніх збурень та явища насичення приводу.
Keywords: Takagi-Sugeno models; actuator saturation; state estimation; actuator faults diagnosis; fault tolerant control; permanent magnet synchronous machine model; linear matrix inequalities; моделі Такагі-Сугено; насичення приводу; оцінка стану; діагностика несправностей приводу; стійкість до відмов; модель синхронної машини з постійними магнітами; лінійні матричні нерівності